Optimalisasi Potensi Sumberdaya Kelautan Sumatera Barat melalui Pemetaan Kualitas Sekolah Menengah Kejuruan (SMK) Kemaritiman - Dwi Astuti (Jurnal Pembangunan Nagari, 2018)
West Sumatra has a large water area with very large potential of marine and fisheries resources but this potential cannot be utilized optimally and sustainably. One obstacle is due to the low quality of Human Resources (HR) in the maritime field. This study aims to map the quality of maritime Vocational Schools in West Sumatra Province in terms of various aspects including facilities and infrastructure, quality and quantity of teaching staff resources, funding and governance followed by policy recommendations for the Government of West Sumatra Province. This research was conducted in August - September 2017 using a qualitative descriptive approach. Data collection was carried out by in-depth interviews and observations in 5 (five) Maritime Vocational Schools in West Sumatra located in Padang City, Agam Regency, Padang Pariaman Regency. Pariaman City, West Pasaman Regency, and South Coastal District. The results showed that the quality of the 5 (five) maritime Vocational Schools was still below the standard when compared to the Middle Fisheries Business School (SUPM) in Padang Pariaman District. The recommendations and policies needed are: collaborating with Universities and Business World / Industrial World that are relevant to optimize facilities and infrastructure, appoint educators as the State Civil Apparatus (ASN) from relevant tertiary institutions and improve their competencies through expertise and financing training support in order to produce reliable maritime HR.